PEMBENTUKAN BADAN PERADILAN KHUSUS DALAM PENYELESAIAN SENGKETA PEMILIHAN UMUM KEPALA DAERAH - Esfandari, Fitria; Oktavia, Adibah; Astri, Isti Latifah (Ahkam: Jurnal Hukum Islam, 2019)
ABSTRACTGeneral elections are the manifestation of democracy. General elections have a close relationship with the formulation of Article 1 Paragraph (1), Paragraph (2), and Paragraph (3) of the 1945 Constitution of the Republic of Indonesia stating that Indonesia is a unitary state, adheres to the people sovereign system, and is a law state. There is no democracy without elections. Therefore, the citizens’ right to choose and to be elected are constitutional rights protected by the Constitution. In its implementation, it still causes many problems. The most fundamental of which is the absence of a special judicial body in resolving the regional election disputes. The purpose of this study is to find out how the Constitutional Court presents the legal certainty as the results of the regional election disputes so far and how the ideal form of the special judicial body is dealing with disputes on regional election results nationally. The author uses a type of normative juridical research with the method of legislative, conceptual, and comparative approaches. Primary and secondary data used are statutory regulations, several jurisprudences, books, and legal journals. In this study, the author hypothesizes that the most ideal form of a special judicial body which handles election results disputes is to establish a special court named the State Administrative Court through the 1945 Constitution amendment mechanism which focuses on handling cases relating to the Executive, including the handling of disputes on regional election results.Keywords: Local Election, Special Judicial Agency,Constitutional Court